Mobile payment transaction on MSMEs - Kusuma, Putu Oka; Darma, Gede Sri (International research journal of management, IT and social sciences, 2020)
The rapid development of technology is driving changes in payment systems in transactions. One payment system is a payment system using a smartphone called Mobile Payment. We can pay attention to Mobile Payment service providers in Indonesia starting to target MSMEs as their target market. This is a very appropriate step considering a large number of MSMEs in Indonesia. This study aims to determine the acceptance of Mobile Payment at MSMEs. By investigating the factors that influence the intention to use Mobile Payment. This study uses descriptive qualitative methods and interpretive through observation, documentation, and interviews with informants. The informants in this study were the MSMEs Owner and Managers in Denpasar. Based on the results of the research conducted, it can be concluded that Mobile Payment has not been fully accepted by MSMEs in Denpasar. Consumers use Mobile Payment because they have partnered with the application, if for offline shopping consumers rarely use and use more cash. The results showed the Perception of Usefulness, Perception of Ease, Perception of Comfort, and Social Influence affect the acceptance of Mobile Payment at MSMEs in Denpasar.